2011
DOI: 10.1007/s13197-011-0244-0
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative potential of folate producing probiotic Lactobacillus helveticus CD6

Abstract: Folate producing Lactobacillus sp. CD6 isolated from fermented milk showed 98% similarity with Lactobacillus helveticus based on 16S rRNA gene sequence analysis. It was found to produce a folic acid derivative 5-methyl tetrahydrofolate (5-MeTHF). The intracellular cell-free extract of strain demonstrated antioxidative activity with the inhibition rate of ascorbate autoxidation in the range of 27.5%±3.7%. It showed highest metal ion chelation ability for Fe 2+ (0.26±0.06 ppm) as compared to Cu 2+. The DPPH (α,α… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 50 publications
(52 reference statements)
1
50
1
1
Order By: Relevance
“…Free hydroxyl radicals are extremely reactive by either removing hydrogen from or adding hydroxyl radicals to biological entities and are also involved in several pathological conditions as well as known for lipids peroxidation and DNA damages (Halliwell and Chirico 1993). Hydroxyl radicals are formed through Fenton reaction by using iron (Ahire et al 2013). DPPH radical scavenging activity of both synbiotic products ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Free hydroxyl radicals are extremely reactive by either removing hydrogen from or adding hydroxyl radicals to biological entities and are also involved in several pathological conditions as well as known for lipids peroxidation and DNA damages (Halliwell and Chirico 1993). Hydroxyl radicals are formed through Fenton reaction by using iron (Ahire et al 2013). DPPH radical scavenging activity of both synbiotic products ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The activity was comparable to present results. Ahire et al (2013) studied antioxidative activity of intact cells and ICFE of L. helveticus CD6. The DPPH activity of intact cells was found to be 24.7 ± 10.9 %, more than the cell extracts (6.8 ± 2.0 %).…”
Section: Antioxidative Activities Of Icfe and Intact Cells Of Probiotmentioning
confidence: 99%
See 1 more Smart Citation
“…They cause cellular oxidative damage that is related to many diseases (Ahire et al, 2013). DPPH is a relatively stable organic radical that has been widely used in the determination of the antioxidant activities of probiotic cell-free extracts (Afify et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Many of the lichen extracts and their metabolites are reported to have variety of biological actions including antioxidative potential (Müller 2001;. Very recently Ahire et al (2011) reported that antioxidant activity of intracellular cell-free extract of a Lactobacillus species. In our study supplementation of lichen metabolites significantly enhanced the growth of L. casei.…”
Section: Resultsmentioning
confidence: 99%